Examining the Relationships between Quality Assurance, Training Need and Choice of Study Destination: A Study of Nigerian Students in UUM - Usman, Abbo; Romle, Abd. Rahim; Qader, Mohammed Mustafa (International Journal of Economics and Financial Issues, 2015)
Several studies identified quality of education as a major criteria influencing international students’ choice of study destination. But only recently has it seems to have gain a huge momentum by emerging as a theme which involves empirical studies. However, despite such momentum previous studies do not provide sufficient evidence linking quality assurance and international student’s choice of study destination. This paper therefore presents a study of international student’s perception of higher education quality assurance practices, as well as how it affects their choice of study destination. The paper tries to examine how training needs play a role in influencing such choice also. The paper through descriptive analysis identified six dimensions of quality assurance in education: “tangibles” “competence” “attitude’ contends”; “delivery”; and “reliability” as well as three dimensions of training needs such “occupational” “organizational” and “individual” needs. Hence it present the inter-relationship between quality assurance, training needs and choice of study destination using the above nine dimension; it concludes with Implications and recommendations to stimulate further studies on study destination choice by the international students from other countries especially from the Arabian and the middle-east. Keywords: Choice of study destination; international students; quality assurance JEL Classification: M00